Writer identity construction in EFL doctoral thesis writing - Daping Wu; Adcharawan Buripakdi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Research on EFL doctoral thesis writing is booming. The literature indicates a link between doctoral thesis writing and identity formation. Despite the call for scholarly attention on doctoral thesis writers, writers of doctoral theses in English as a Foreign language (EFL) settings have not been well represented in the previous studies. Moreover, although writer identity has been proposed as consisting of four aspects, most of the research has mainly adopted a corpus approach to discuss the discoursal self or authorial identity. To bridge these gaps, this study explored how multicultural writers at a university in Thailand constructed identity through EFL doctoral thesis writing and how their multiple aspects of writer identity interplayed. With the data triangulated from a questionnaire, written narratives, and semistructured interviews, the study revealed that 1) multiple identities are developed through writers’ self-adjustment and social acculturation; 2) passive alignment to institutional conventions leads to an actual distancing from discoursal construction of writer identity; 3) self-marginalization as EFL learners, negative external voices, and the role of student writer most hinder the development and representation of the authorial self. The research recommends EFL learners should be explicitly informed of the notions of constructing an authorial voice in the writing of doctoral theses.